CRITICAL SUCCESS FACTORS TO TAX ADMINISTRATION EFFICIENCY IN NIGERIA: EVIDENCE FROM BAUCHI STATE BOARD OF INTERNAL REVENUE (Malaysian Management Journal, 2017)
This study investigates the determinants of tax administration efficiency in Nigeria. The Nigerian tax system is faced with challenges, such as loss of revenue through high level of tax defaulters from both the legislative arm of the government and public institutions, corruption and financial irregularities and limited government administrative capability. Therefore, current study examines the influence of autonomy of the State Board of Internal Revenue (SBIR), use of information and communications technology, public enlightenment, strong auditing practice, motivation and incentives and perceived corruption on tax administration efficiency in Nigeria. A total of 124 questionnaires were collected out of 144 questionnaires that were administered. The study revealed that there is a significant positive relationship between tax administration efficiency and: autonomy of board of internal revenue, information and communications technology and public enlightenment. However, findings from the study revealed that there is insignificant relationship between tax administration efficiency and strong audit practice and motivation and incentives and perceived corruption. Based on the findings above, the study recommended that government should put an effective measure in place to collect taxes from tax defaulters across the different groups of the economy.